2021
DOI: 10.31459/turkjkin.861920
|View full text |Cite
|
Sign up to set email alerts
|

Development of explosive power in basketball players

Abstract: Basketball is a very active sports game with frequent changes of speed, a large number of jumps and active use of all muscle groups. The aim of this review is to identify, analyze and explain all significant components for the development of explosive power in basketball players. The results showed that despite the high coefficient, which is congenital, explosive power can be developed through well-organized training which should be conducted methodically, rationally and in a well-organized manner. For quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 42 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Power in basketball is a multifaceted attribute that influences the performance of players in numerous ways. Powerful players can be more imposing defensively, challenging shots, guarding multiple positions, and providing help defence ( Aksovic et al, 2021 ). The results showed that FT had a significant improvement in upper limb power (throwing the medicine ball) ( Hany, 2017 ) and anaerobic power (running-based anaerobic sprint test) ( Hovsepian et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Power in basketball is a multifaceted attribute that influences the performance of players in numerous ways. Powerful players can be more imposing defensively, challenging shots, guarding multiple positions, and providing help defence ( Aksovic et al, 2021 ). The results showed that FT had a significant improvement in upper limb power (throwing the medicine ball) ( Hany, 2017 ) and anaerobic power (running-based anaerobic sprint test) ( Hovsepian et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Explosive power, an ability to generate maximum muscle strength in the shortest possible time (Santos & Janeira, 2008) is an extremely important motor ability to play basketball (Lehnert et al, 2013;Aksović et al, 2020a;Aksović et al, 2021). Vertical jumps are often used to estimate the explosive power of the lower extremities.…”
Section: Effects Of Plyometric Training On Explosive Powermentioning
confidence: 99%
“…Athletes of the same specialty still have high and low qualities. In addition to a technical level, the level of muscle is also examined, because muscles are the source of power for competitive athletes [6]. This study applies Panjabi's concept of axial stability and the spinal peripheral muscle system as its basis [7] because the spinal peripheral muscle system is the active subsystem used by the body to generate force.…”
Section: Introductionmentioning
confidence: 99%